Responsive strategies of agricultural water sector in Taiwan - Cheng, Chang-Chi, author; Kan, Chun-E, author; Chuang, Kuang-Ming, author; Jan, Ming-Young, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2007)
In addition to increasingly frequent water shortage problems, agricultural water sector is also challenged by environmental issues. The objective of this article is to summarize, as well as propose sustainable strategies for agricultural sector in response to current environmental challenges. For water shortage problems, which are becoming more and more frequent worldwide including Taiwan, measures for irrigation water, such as extending irrigation periods, decreasing number of irrigation application times, or rotational irrigation, are introduced and discussed. When borrowing or transfer of water among sectors is needed in Taiwan, it is usually from agricultural irrigation water to other sectors in almost all cases. The maintenance of water right, and compensation to farmers for their income loss, are the two major issues. As for environmental changes, the impact of the accession of Taiwan to WTO (World Trade Organization) is discussed specifically in this article, and a management scheme in order to save irrigation water, which could be used for other purposes, is suggested in this article.
USCID fourth international conference
Not digitized by CSUL Digital Services.
Presented at the Role of irrigation and drainage in a sustainable future: USCID fourth international conference on irrigation and drainage on October 3-6, 2007 in Sacramento, California.